Analisis Literasi Matematika dalam Menyelesaikan Soal Berorientasi PISA Konten Quantity pada Siswa SMA ditinjau dari Perbedaan Jenis Kelamin - Dewi Putri Sari; Sudargo Sudargo; Muhtarom Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to determine how the analysis of mathematical literacy in solving quantity content PISA-oriented questions for high school students in terms of gender differences. This type of research is descriptive qualitative research. This research was conducted at SMAN 1 Tanjung Brebes Regency in 2020/2021. The subjects of this study were six students of class X MIPA representing groups of mathematics literacy test results (low, medium, and high) and of different genders. The subjects in this study used a purposive sample technique, which was determined based on the results of written mathematical literacy tests and gender. The data was collected through a mathematics literacy test oriented to the quantity content PISA and interviews. Meanwhile, the triangulation used in this study was method triangulation. The results showed that female students had better mathematical literacy than male students on 2 of the 4 indicators of mathematical literacy. Overall, female’s mathematical literacy is superior than male students.